Experiências investigativas da prática docente: as oficinas pedagógicas como contribuição para autoformação de professores em contexto de ensino tecnológico - Silva, Daniel Mota da (2022)
This research is configured in a perspective of teacher self-training in conjunction with pedagogical practice, as a contribution to the re-dimensioning of teachers in the technological context. In this sense, I emphasize as the object of this research teacher self-training and its presuppositions in pedagogical practice, considering the teacher's autonomy, the possibilities of overcoming and breaking paradigms regarding teacher training, as well as self understanding, in order to consider its ipseity and the context of technological education. In the theoretical reflections undertaken in this study, we make use of the contributions of authors who emphasize the importance of a critical-reflexive formation relevant to the development of the teaching subject, in his/her condition of protagonist of his/her professional path. Ratifying the training of teachers concomitantly with the methodology based on autobiographical letters in order to subjectively analyze the observed phenomena, in order to provide a self-reflection on their itinerary. The process experienced throughout this research allowed the organization and implementation of an educational product entitled: "Connections of teaching practices: a pedagogical workshop to tell yourself and resignify yourself as a teacher", as a pretext for recognizing the importance of self-training to qualify as a teacher. That in the problematization of the investigated object we dialogued with professors, who exposed relevant information about their professional experiences with a focus on the object of study. In the process of data analysis, we were guided by the technique of content analysis of triangulation, which was carried out seeking not to reduce the meanings of the constructed reports. In this perspective, the research results recognize that self-training is part of the teaching professional itinerary, which values creativity and reflective action regarding the (re)vision and reorientation of pedagogical activities. In which it effectively allows the teacher to discuss and (re)think autonomously, the decisions to be taken in the face of the intemper and the demands that arise in their professional path, allowing them to have a critical and conscious apprehension of the pedagogical practice carried out in the process of teaching.